Stakeholder Engagement and Integration into the Framework - Nicola Jentzsch (Waterford Institute of Technology (WIT), 2015)
This document is an IPACSO service document for the European Commission. It's main purpose is to outline the contribution and integration of work package 4 into the IPACSO framework. Moreover, it explains stakeholder engagement and the economic incentivization techniques for enabling the adoption of the IPACSO framework. Due to the fact that such incentivization is not directly related to a market and incentives analysis, it was set aside in order to obtain an extra document (deliverable), which is also explicitly mentioned in the IPACSO Description of Work.
info:eu-repo/grantAgreement/EC/FP7/609892
Keywords: 650; Datensicherheit; Marktanalyse